THE USE OF WORDWALL MEDIA TO IMPROVE STUDENTS’ VOCABULARY AT TENTH GRADE OF SMK NEGERI 1 SITOLUORI - Zega, Yuslinda Sari; Maru'ao, Nursayani; Harefa, Trisman; Harefa, Afore Tahir (Universitas PGRI Palembang, 2025)
This study explored the effectiveness of Wordwall Media in enhancing vocabulary acquisition among tenth-grade students at SMK Negeri 1 Sitoluori through a Classroom Action Research (CAR) approach conducted over two cycles. The findings revealed a marked improvement in vocabulary, assessed across three domains: spoken, written, and meaning. Initial pre-test scores showed averages of 52.72 (spoken), 29.63 (written), and 28.63 (meaning). In Cycle I, scores rose to 73.63 (spoken), 75 (written), and 49.09 (meaning), and further improved in Cycle II to 84.09 (spoken), 86.81 (written), and 84.09 (meaning). The use of Wordwall Media significantly supported vocabulary development by offering interactive and visually engaging content, such as animations and images, which enhanced student comprehension and motivation. The study concludes that integrating Wordwall Media into English instruction effectively addresses students’ vocabulary challenges. Teachers are encouraged to adopt this tool consistently to foster a more dynamic and effective learning environment.